Análise do comportamento termomecânico e da evolução microestrutural durante a laminação de tiras a quente de aços C-Mn via DEFORM™ 3D - Souza, Antonio Lourenço Batista de (2015)
Improving the steel processing is a major focus of the metallurgical industry because the need of materials and products with lower weight and more strength, in addition to increasingly stringent specifications imposed by buyers. The knowledge and kinetic control of the phenomena that occur during hot processing such as recrystallization, precipitation and grain growth are mandatory for the grain size refinement, which is a parameter that determines the properties of semi-finished products. In hot strip rolling the material is subjected to deformation schedules consisting of five to seven passes, with rolling mill arranged one in front of the other, performing a continuous operation. Over the years, several paths have been followed to investigate the industrial processing. One can cite as examples the use of pilot plants, physical simulations, and numerical simulations. The objective of this study was, therefore, to model the process of the hot strip rolling, enabling the analysis of how the process parameters such as temperature, strain, strain rate and austenitic grain size evolve during rolling of the C-Mn steels, using the commercial software DEFORM™ 3D developed for forming processes analysis. Seven rolling passes of an industrial process described were simulated. The results shown a good agreement of the load and temperature levels attained during simulation with the literature values, indicating that the model used to represent the industrial rolling process is suitable. The numerical reconstruction of processing shows clearly the presence of the strain, temperature and strain rate gradients during hot strip rolling mill, generating microstructural gradients. The evolution of rolling process minimizes the gradients, but some ones still remain at the end of rolling process. Thus, this study shows the effectiveness of the model to predict the evolution of the microstructure in a hot rolling process.